2015
DOI: 10.1016/j.nut.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

A single FTO gene variant rs9939609 is associated with body weight evolution in a multiethnic extremely obese population that underwent bariatric surgery

Abstract: There is a different evolution of weight loss in obese carriers of the FTO gene variant rs9939609 after bariatric surgery. However, this pattern was evident at only 2 y postbariatric surgery, inducing a lower proportion of surgery success and a greater and earlier weight regain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
0
19
1
1
Order By: Relevance
“…These findings may explain our borderline association of the rs9939609 with the BMI; however, this needs to be replicated further in other cohorts in the population. The FTO variant has been reported to be involved in weight regain after bariatric surgery [23] which is considered a common obesity intervention in the Kuwaiti population [24], and therefore identifying patients at high risk of weight regain prior to intervention may help in planning the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may explain our borderline association of the rs9939609 with the BMI; however, this needs to be replicated further in other cohorts in the population. The FTO variant has been reported to be involved in weight regain after bariatric surgery [23] which is considered a common obesity intervention in the Kuwaiti population [24], and therefore identifying patients at high risk of weight regain prior to intervention may help in planning the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of the important function of LHX3 on animal growth and reproduction, the associations between the 29 bp indel and the sheep growth traits were also analyzed. An interesting phenomenon was found in Tong sheep body length and chest width growth traits: the individuals with the II genotype showed superior traits, and the individuals with the homozygote II genotype were significantly better than those with the ID genotype; that is, the II genotype was the most conducive to growth in Tong sheep, which was a potential genetic marker used to improve Tong sheep breeding (Tepaamorndech et al, 2014;Rodrigues et al, 2015). In fact, many studies have also reported that the indel within critical genes was associated with growth traits in livestock.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP of the FTO gene that was commonly investigated regarding weight regain was rs9939609, but the results were inconsistent. Specifically, three previous studies, which include a study in children, showed that the A allele of that SNP was positively associated with weight regain (51)(52)(53) . On the other hand, a study in postmenopausal females and another two studies in subjects with impaired glucose tolerance and type 2 diabetes found there was no relationship of that SNP with weight regain (23,24,54) .…”
Section: Nutrient Metabolism-related Genes and Their Association Withmentioning
confidence: 99%